2 Laws of New Hampshire: Province Period 284-85 (Albert Stillman Batchellor ed., 1913) - (:unkn) unknown (My University, 1704)
"All Male Persons from Sixteen Years of Age to Sixty [] shall bear Arms." The primary arms mandate applied to "every Listed Souldier and Housholder (except Troopers)." In other words, the head of a house was required to have the specified arms, even if the head were not militia-eligible. These arms were "a well fix'd, Firelock Musket, of Musket or Bastard-Musket bore, the Barrel not less than three foot and a half long; or other good Fire-Arms, to the satisfaction of the Commission Officers of the Company." Now, the mandatory equipment included gun cleaning tools: "a Worm and Priming Wire fit for his Gun." Mandatory edged arms were "a good Sword or Cutlash." As for horsemen, they needed "a Carbine, the Barrel not less than Two Foot and half long, with a Belt and Swivel, a Case of good Pistols with a Sword or Cutlash, a Flask or Cartouch Box, One Pound of good Powder, Three Pound of sizeable Bullets, Twenty Flints, and a good pair of Boots, and Spurs.
Keywords: MILITIAS; REQUIRED POSSESSION